A market research on challenges influencing artificial intelligence adoption - Schmiegelow, Fernando; Melo, Francisco C. L. (Business: Theory and Practice, 2023)
Although there are many theoretical references regarding the adoption of artificial intelligence, its practical challenges remain unknown. This article uses a market research aiming to identify the critical success factors to prepare for the artificial intelligence implementation, indicating the most appropriate strategies to adddress them. The results allow us to conclude that there are several challenges, the main ones being the lack of data infrastructure and trained people, and the lack of a better understanding of applications. Artificial intelligence, as well as other disruptive technologies, makes room for rethinking business models, not only improving existing processes, but also making it possible to see new opportunities. It is interesting to point out that, much more than a simple innovative project to improve processes and business, a succesful artificial intelligence implementation enables the creation of a new culture of interaction, experimentation, automation, analysis and prediction.